Humic acids bioactivity: effects on root development and on the plasma membrane proton pump - Rocha Façanha, Arnoldo; Lvovna Façanha, Anna Okorokova; Olivares, Fábio Lopes; Guridi, Fernando; Santos, Gabriel de Araújo; Velloso, Ary Carlos Xavier; Rumjanek, Victor Marcos; Brasil, Felipe; Schripsema, Jan; Braz-Filho, Raimundo; de Oliveira, Marco Antônio; Canellas, Luciano Pasqualoto (Pesquisa Agropecuaria Brasileira, 2002)
The bioactivity of humic acids (HA) isolated from sludge of the station of sewer treatment (HAL) and from vermicompost (HAV) was evaluated through the action of those substances on primary transport of protons of the plasma membrane of coffee and corn root cells and its relationship with the development of those species. A stimulation in the superficial area of roots was observed for both species cultivated with both humic acids, exhibiting an optimum concentration, about 40 mg L-1 of HA. In this condition the treatment with HAL and HAV stimulated the plasma membrane H+-ATPase of corn and coffee roots. HAL were more effective to promote those effects than HAV. The modification of the chromatographic profile of the HA in solution before and after the cultivation of the seedlings revealed that the interaction plant-HA promoted a rearrangement of the average molecular weight of those substances suggesting a dynamic mobilization of bioactive subunits of the HA by plant exudates. The structural analysis of the HA has detected the presence of auxin groups. A comparative analysis of the action of those HA on the monocotyledonous (corn) and dicotyledonous (coffee) plants indicates to the activation of plasmallema H+-ATPase as a possible metabolic marker for bioactivity of humic acids.